Verifikasi dan Validasi Kelompok Usaha Mandiri (Kum) dalam Rangka Penilaian Proper PT. Indonesia Power UPJP Kamojang - Mochamad Romdhon; W Widaningsih (Jurnal Wacana Ekonomi, 2018)
This study is intended to determine the progress of the implementation of the Inpower-CARE Program of PT. Indonesia Power UPJ Kamojang towards increasing added value for independent business groups in the area around the company. The purpose of this program is to determine the company's performance on program implementation which is a measure of the success in implementing the CSR program of the company concerned. The research method used is a qualitative method by prioritizing 2 approaches, namely a documentation study conducted with a field survey and a literature study, with the intention of comparing field data with theoretical views. The results showed that the implementation of the program Inpower-CARE PT. Indonesia Power UPJ Kamojang is said to be quite effective in providing added value for Business Actors around the Company. From this result, of course, it has its weaknesses because it is viewed from the point of view of the organization as a whole and it is necessary to carry out further research so as to produce in-depth conclusions about the effect of this.